Reduction Of Switching Activity In Noc By Using Data Encoding Schemes (International Journal of Engineering and Computer Science, 2015)
As technology shrinks, the power dissipated by the links of a network-on-chip (NOC) starts to compete with the power dissipated by the other elements of the communication subsystem, namely, the routers and the network interfaces (NIs). In this paper we present a reduction of switching activity in network on chip (NOC) by using data encoding schemes. In proposed schemes there is no need to change link architecture and it will reduce transitions (i.e. nothing but switching activity contains both switching transitions and coupling transitions).due to these transitions lot of power consumption is presented at the network on chip and routers so that by using data encoding schemes we can save  consumption of energy and dissipation of power without any degradation of performance .